Persepsi Pemustaka terhadap Layanan Front Office Universitas Andalas - Mulhairi, Mulhairi; Marlini, Marlini; Desriyeni, Desriyeni (TSAQOFAH, 2026)
The Front Office is the frontline service unit that plays a strategic role in shaping library users’ service experiences in academic libraries, including the Andalas University Library, where interactions between staff and users are highly intensive. This study aimed to analyze users’ perceptions of the service experiences they receive at the Front Office of the Andalas University Library by drawing on theories of perception, service quality (SERVQUAL), and service experience. The method employed was a literature study with descriptive analysis of works related to library services, service quality, and user behavior. The findings indicate that users’ perceptions of the Front Office are shaped by several key factors, namely staff interpersonal communication competence, clarity of information, speed and accuracy of service procedures, staff professionalism in addressing users’ needs, and the quality of the Front Office’s physical facilities; these factors jointly contribute to the formation of both positive and negative service experiences. The study underscores the importance of strengthening service standards, enhancing staff competencies, optimizing service information, and developing Front Office physical facilities as key strategies for improving users’ perceptions of and satisfaction with services at the Andalas University Library as a whole.